Cadbury's Dairy Milk / Ayu Farzil Wanee Sulaiman ... [et al.] - Sulaiman, Ayu Farzil Wanee; Ismail, Ira Sharmilla; Bakri, Nazinordina; Hamdan, Norazwa (2016)
The new milk chocolate was introduced to the British market in 1905 and, with its unique flavor and texture, quickly became the market leader. Milk chocolate was first made by Cadbury in 1897 by blending milk powder with the basic chocolate ingredients of cocoa butter, cocoa mass and sugar. By today's standards the chocolate wasn't particularly good because it was very coarse and dry and neither sweet nor milky enough. At that time, the Swiss dominate the milk chocolate market with a product of superior taste and texture produced by Daniel Peters of Vevey, using condensed milk rather than milk powder. In the early 1900s, George Cadbury Junior and experts at Bournville took on the Swiss, researching new recipes and production methods. By June 1904, the recipe was perfected and a delicious rich and creamy new milk chocolate was ready for production.